Cushing Syndrome Cardiomyopathy: Clinicopathologic Impact of Cortisol Normalization. (April 2016) - Frustaci, Andrea; Letizia, Claudio; Verardo, Romina; Grande, Claudia; Petramala, Luigi; Russo, Matteo Antonio; Chimenti, Cristina
Abstract : Supplemental Digital Content is available in the text.